The Influence of Budgetary Participation on Managerial Performance with Distributive Fairness, Procedural Fairness, and Budget Goal Commitment as Mediating Variables - Denardo Denardo; Sudarwan Sudarwan (Journal of Multidisciplinary Academic, 2019)
One of the factors used to improve organizational effectiveness can be seen from its managerial performance. Management functions that include planning, organizing, coordinating, evaluating, supervising, selecting staff, negotiating and representing to represent the basis of planning so far managers can do these things to see the development of management in the organization. It is said, effective in financial planning related to the budget issued and provide opportunities for subordinates to be approved or involved in the budgeting process. In previous studies concerning budgetary participation in managerial performance, it was concluded that the results were still changing or inconsistent. This requires other variables that influence budgetary participation and managerial performance. The purpose of this study is to study the effect of budgeting on managerial planning with distributive justice, procedural justice, and commitment to budget objectives as mediating variables. This research was conducted in 2019. Data collection techniques were carried out by distributing questionnaires to 35 manager-level employees and above at BCS Logistics as a respondent. Respondents was selected by purposive sampling method in which the respondents should have level manager position above, minimum of one-year experience in that position, and involved in the making of budget. The analysis technique used in this study is Partial Least Square (PLS). The instruments have been examined for its validity and reliability. Statically analysis showed that distributive fairness, procedural fairness, and budget goal commitment could be a mediating variable in the relationship of budget participation on managerial performance.